Renal epitheliotropism of feline morbillivirus in two cats - Chaiyasak S. (2023)
The association of feline morbillivirus (FeMV) with kidney disease in cats is controversial. Two cats with a history of severe hematuria had eosinophilic inclusion-like bodies in the renal tubular epithelial cells, without any inflammatory cellular reaction. Ultrastructurally, aggregations of electron-dense viral-like particles were found where the inclusion-like bodies were located. Immunohistochemistry (IHC) using antibodies against FeMV matrix protein labeled these inclusion-like bodies, and also labeled the cytoplasm of tracheal and bronchiolar epithelial cells, and lymphocytes and macrophages in spleen and mesenteric lymph node. Using double IHC, FeMV antigen was detected in astroglia and oligodendroglia but not in microglia. Phylogenetic characterization of the fusion and hemagglutinin gene sequences revealed FeMV-1A genotypes in both cats. These findings indicated an active viral infection with FeMV. We propose that FeMV is a renal epitheliotropic virus and also localizes in various other tissues.